Religious Values in The Poem "Senja" by Subagio Sastrowardoyo and its Implementation with Character Education as Literature Teaching Material in High School - Kumalaningdyah, Maharani; Markhamah, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to describe the religious values contained in Subagio Sastrowardoyo's Twilight poetry and implement the religious values contained in Twilight poetry by studying literature in high school as character education. The object of this research is the religious value in the Twilight poetry by Subagio Sastrowardoyo. This research is a type of descriptive qualitative research with content analysis. The data in this research are words and sentences. The data comes from the Twilight poem by Subagio Sastrowadoyo. The data collection technique uses the library, listen, and note techniques. The data analysis technique uses interactive techniques with a stylistic approach. Based on the research results, it was found that religious values between humans and the natural environment are in the form of humans' feelings of hatred for things that are beautiful but only temporary and human relationships with other humans, namely humans' fear of being separated from other humans and the fear of losing. The results of the research can be implemented in literature learning in high school because the religious values contained in the poetry are related to students' character education. Based on the research results, the religious values that researchers found contained in Subagio Sastrowardoyo's poems can be said to be relevant to literary learning. The value of character education is the experience and appreciation aspect, the knowledge aspect, and the behavioral aspect.